PENGGUNAAN MEDIA VIDEO UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN : Studi Deskriptif di Kelas XII SMKN 2 Sumedang - Hasna Latifah, - (2019)
This research is motivated by the low level of critical thinking skills of students in schools, indicated by the inactivity and responsiveness of students in the learning process in the classroom. In addition, many PPKn teachers still use lectures as learning methods. The purpose of this study is to obtain a clear picture of the efforts of teachers to improve students' critical thinking skills in learning PPKn using media video. The research approach used by researchers is a qualitative approach with descriptive methods. Therefore, the authors want to describe the use of video media in preparing the planning and implementation of learning, the response of students to the use of media video, as well as improving students' critical thinking skills after using media video. The results of the study indicate that: (1) in the preparation of learning plans carried out by PPKn teachers, namely by inserting media video into RPP; (2) in the implementation of learning carried out by using media video and scientific approaches, namely by implementing activities 5 M; (3) responses of students who become active in learning PPKn using media video; (4) there is an increase in critical thinking skills after using media video.